FRI0154 Low dose etanercept in moderate active rheumatoid arthritis - a pilot study: Induction and maintenance of clinical and radiographic remission. (23rd January 2014) - Raffeiner, B.; Botsios, C.; Canova, M.; Sfriso, P.; Ometto, F.; Bernardi, L.; Vezzari, C.; Stramare, R.; Todesco, S.; Punzi, L.
Abstract : Background: Patients with rheumatoid arthritis (RA) and moderate disease activity may achieve generally better clinical outcomes with etanercept (ETA) treatment than patients with high disease activity, including significant differences in DAS28 remission, low disease activity, and HAQ [1]. Low dose ETA is shown to be effective in moderate active RA [2, 3]. Objectives: To evaluate efficacy of low dose ETA in the induction and maintenance of clinical and radiographic remission in moderate active RA. Methods: Prospective observational cohort study was performed at the Rheumatology Unit of the University of Padova (Italy) between 2004 and 2010 on consecutive RA patients naive for biologic agents with moderate disease activity as defined by DAS28 (3.2 to 5.1) unresponsive to DMARDs therapy. Thirty-eight patients (34 female and 4 male, age 57.3±14.3, disease duration 10.7±7.2, DAS28 4.4±0.6) were treated with low dose ETA (25 mg once a week) as induction and maintenance therapy. This group was compared with 36 patients starting and continuing standard dose (25 mg twice a week) as control group. Patients not reaching DAS28 remission within 6 months were considered unresponsive. Rates of patients reaching and then maintaining DAS28 until the end of 18 treatment months were compared between groups. Baseline characteristics were compared between groups. Modified Sharp score/van der Heijde (TSS) was performed on hand and feet x-rays at month 6 and after one year at month 18. Radiographic progression was defined as ΔTSS >0 and was compared between groups. Statistical analysis was performed with SPSS using Pearson's test, exact Fisher's test and Student T test as appropriate. Results: Low dose ETA induced DAS28 remission in the majority of patients with moderate disease activity (94.7%), and was as effective as the control group started with standard dose (94.5%; p = ns). After 18 months rates of survivorship of DAS 28 remission were the same for the two groups (78.9% vs 80.5%; p = ns) as it was for radiographic progression (9.1% vs 11.1%; p = ns). Baseline characteristics including age, sex, disease activity and duration, autoantibodies, ΔTSS/year, HAQ, concomitant and past therapy with DMARDS, steroid and FANS were not different between groups (p = ns). Conclusions: Our study suggests that low dose ETA is effective in the induction and maintenance of DAS28 remission in moderate active RA without greater loss of efficacy or progression of radiographic damage in time. References: Keystone E, Freundlich B, Schiff M, Li J, Hooper M. Patients with moderate rheumatoid arthritis (RA) achieve better disease activity states with etanercept treatment than patients with severe RA. J Rheum 2009;36(3):522-31. Goodman A. Half-dose etanercept effective at 1 year in RA. ACR 2011: Abstract L1. Presented November 8, 2011. Raffeiner B, Botsios C, Sfriso P, Ometto F, Bernardi L, Todesco S, Punzi L. Efficacy of low dose etanercept in maintaining clinical and radiological remission in rheumatoid arthritis. Ann Rheum Dis 2010;69(3):102. Disclosure of Interest: None Declared